The Challenges of Developing Smart House - Jiding, Josielyn; Shareh Musa, Sharifah Meryam; Kasim, Narimah; Zainal, Rozlin (Research in Management of Technology and Business, 2024)
The development of smart houses has grown in significance as the search for environmentally friendly and energy-efficient built environment solutions continues. However, higher construction costs, low smart house development, lack of awareness, and insufficient research present notable challenges to the widespread adoption of these technologically advanced residential spaces. In "smart" homes, advanced technology is used to optimize operations, increase energy efficiency, and improve tenant comfort and safety. This research aims to explore developers’ perceptions of smart house development, identify challenges in developing smart houses, and identify strategies to address these issues. The study is focusing on residential smart houses, particularly smart homes. Qualitative methods, including interviews with 3 respondents, were employed to collect information and examine the opinions and experiences of developers in the area. The method used for data analysis is content analysis. The findings reveal that developers perceive operational efficiency in smart houses, utilizing features like motion sensors and air conditioner temperature management to perceptibly reduce electricity consumption. The readiness for smart housing is influenced by customer feedback, budget considerations, and market demand. Challenges encompass higher construction costs, project complexity, and a lack of awareness. Smart house development is a relatively new concept, the low demand contributes to higher costs compared to conventional houses. To address challenges, strategies involve conducting cost analysis, comparing material functionality and costs, and hiring experienced stakeholders for successful execution. Emphasis is placed on proper planning, including resource allocation and device integration. By addressing the issues and challenges faced by developers in the sector, this study ultimately aims to facilitate the sustainable growth of smart houses in Malaysia.